Acute exposure to TiO2 nanoparticles produces minimal apparent effects on oyster, Crassostrea virginica (Gmelin), hemocytes. (February 2018) - Doyle, John J.; Ward, J. Evan; Wikfors, Gary H.
Abstract: The response of oyster ( Crassostrea virginica ) hemocytes was studied following exposure to anatase nanoparticles (ca. 7.4 nm), surface-coated rutile nanocomposites (UV–Titan M212, ca. 86 nm) and bulk titanium dioxide (TiO2 ) particles (anatase and rutile crystalline forms; 0.4-0.5 μm). Hemocytes were collected from oysters and exposed to one of the four particle types at concentrations of 0.1, 0.5, and 1.0 mg/L under dark and environmentally-relevant light conditions for periods of two and four hours. Hemocyte mortality, phagocytosis, and reactive oxygen species (ROS) production were then evaluated using flow-cytometric assays. Bulk and nanoparticulate TiO2 had little effect on viability of oyster hemocytes or on production of ROS. Significant changes in phagocytosis occurred after exposure to anatase nanoparticles for 4 h under dark conditions, and UV–Titan for 2 h under light conditions. Results demonstrate that TiO2 particles (bulk or nanoscale) produce minimal effects on hemocyte biomarkers examined following acute, in vitro exposures. Highlights: The effects of titania nanoparticles on oyster ( Crassostrea virginica ) hemocytes was investigated. Cells were exposed to anatase and UV–Titan M212 nanoparticles at 0.1, 0.5, and 1.0 mg/L. Exposures included dark and light conditions for periods of two and four hours. Few effects on mortality, phagocytosis, and reactive‑oxygen-species production were detected. Titania nanoparticles produced minimal effects on biomarkers examined following acute, in vitro exposures.